Komodifikasi Kesalehan: Kosmetik Halal, Brand Islam, dan Identitas Muslimah Indonesia - Astriani, Dini (Fakultas Syariah IAIN Kerinci, 2025)
Halal cosmetics in Indonesia have experienced rapid growth, driven by increasing consumer awareness of sharia compliance, ethical lifestyle, and spiritual identity. This study aims to explore how religious symbols are represented and commodified in the marketing and consumption of halal cosmetics by Muslim women in urban Indonesia. Using the theoretical framework of Brand Islam combined with gender performativity theory, the research applies visual content analysis and critical discourse analysis to promotional materials from Wardah, Emina, and Safi (2021–2025), supported by interviews with Muslim women consumers and secondary data from regulatory institutions. The findings show that halal cosmetics function as tools for expressing modern religiosity, aesthetic aspirations, and identity formation among middle-class Muslim women. However, the study also reveals ethical dilemmas in religious branding, particularly regarding transparency and the potential reduction of piety into market symbolism. These insights contribute to the broader discussion on the intersection of faith, consumer culture, and the halal economy.